Rapid weight loss alters muscular performance and perceived exertion as well as postural control in elite wrestlers - Jlid, M.; Maffulli, N.; Elloumi, M.; Moalla, W.; Paillard, T. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim was to assess the effects of rapid decline of body mass on postural control, muscular performance and rating perceived exertion in elite free style wrestlers. Methods: Ten high-level wrestlers (age: 19.3±2.5 years, height: 175.7±4.9 cm, body mass before dieting: 77.16±11.94 kg) are included in the present study. Diet was monitored for all the athletes. Athropometric measurements and a variety of functional tests such as isometric hand grip strength (IHG) and isometric back strength (IBS) with dynamometers, dynamic postural control (DPC) with star excursion balance test, and rating of perceived exertion (RPE) to a standard exercise of knee pushups, were performed before and after diet completion. Results: The diet was based on food restriction and dehydration. Body mass, lean body mass and body water significantly decreased (PConclusion: Previous studies showed that the rapid decline of body mass affects health and muscular and energetic performance while the present study highlights that it also alters perceived exertion and dynamic postural control.